The Effect of Pegword Method on the Students’ Ability in Mastering Vocabulary at the Eighth Grade of SMP Negeri 1 Lahewa Timur - Zalukhu, Ikardi; Harefa, Hasrat Sozanolo (Edumaspul: Jurnal Pendidikan, 2024)
Vocabulary is central to language and crucial for effective communication, both orally and in writing. Insufficient vocabulary hinders students’ ability to express themselves. Recognizing this challenge, a researcher investigated the efficacy of the Pegword Method in enhancing vocabulary acquisition among eighth-grade students at SMP Negeri 1 Lahewa Timur in 2020/2021. This quasi-experimental study involved a population of 60 students, selected using Cluster Sampling Technique. Pre-test results indicated comparable vocabulary levels between the experimental and control groups. The experimental group received Pegword Method instruction, while the control group received Conventional Teaching Method. Post-test results revealed significant improvement in the experimental group, with a mean score of 79.33 compared to 68.33 in the control group. Statistical analysis confirmed the effectiveness of the Pegword Method, with t-count (2.39) exceeding the critical value (2.002). Therefore, the null hypothesis was rejected, indicating a significant positive impact of the Pegword Method on vocabulary mastery.Suggestions for educators include implementing the Pegword Method to enhance vocabulary instruction and fostering student motivation through engaging materials and ample library resources. Further research in this area is recommended to enrich teaching practices and optimize student learning outcomes.